Uma política de controle dinâmico de estoques em uma cadeia de suprimentos serial com incerteza na demanda de mercado usando eventos discretos - Pacheco, Eduardo de Oliveira (2017)
The inventory control policy is a challenge in supply chain operation. It has to maintain inventory stability by avoiding amplification of the market demand in the supply chain levels while keeping good custom service. The inventory control policy determines the correct time (reorder point) and quantity (lot size) to fill inventories of the supply chain levels. This thesis proposes a new procedure to update both reorder points and lot sizes for an inventory control policy Order-Up-To-Level (OUTL) in continuous review systems. The new procedure modifies the classical OUTL policy by introducing the concept of absorption inventory characterized by the market demand and lead time in each chain level. This procedure updates order points and lot sizes when particular events have occurred. A mono-product supply chain composed by three levels (retailer, distribution, and manufacturing) is simulated by a discrete event simulation considering uncertainty in demand. The supply chain performance is evaluated by several metrics taking into account the bullwhip effect, customer service level, responsiveness, inventory level and stock out, and lot sizes and reorder points. The results show that the bullwhip effect and lot size variability are reduced, service level is improved, and inventories are stable when compared with the classical OUTL policy.